2014
DOI: 10.2340/00015555-1665
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Three-year Longitudinal Study of Melanocytic Naevus Development in Pre-school Children in Dresden, Saxony

Abstract: Acquired melanocytic naevi (MN) are considered a risk factor for melanoma. Exposure to ultraviolet light (UV) is the major environmental factor for MN. UV protection is most critical in pre-school children. This 3-year interventional longitudinal study examined 395 3-year-old children attending daycare centres (DCC) in Dresden, Germany. Photo-skin type, eye and hair colour were recorded. DCC were randomly assigned to a control group and a behavioural intervention group. All children had a regular naevus check-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Observations in these studies support the need for consistent counselling with children and their parents regarding the appropriate use of sun protection, which is also confirmed by other studies . Moreover, environmental interventions, such as the use of shade structures, are also required to support educational lessons , besides combined behavioural and political interventions .…”
Section: Discussionsupporting
confidence: 74%
“…Observations in these studies support the need for consistent counselling with children and their parents regarding the appropriate use of sun protection, which is also confirmed by other studies . Moreover, environmental interventions, such as the use of shade structures, are also required to support educational lessons , besides combined behavioural and political interventions .…”
Section: Discussionsupporting
confidence: 74%
“…Recent studies have suggested that significant increases in melanocytic nevi counts in preschool children call for improved ultraviolet protection, but knowledge does not automatically change behavior. 65 The use of any management decision in children with familial melanoma should be tempered by the findings of a recent study, where atypical nevi in childhood, the nevus count of atypical nevi on the buttocks, and most importantly, the number of excisions during follow-up correlated with the risk of melanoma. 66 In Caucasian skin, it is believed that the total number of CAMN on the whole body is the most important independent risk factor for melanoma, and the risk of melanoma development increases almost linearly with rising numbers of melanocytic nevi.…”
Section: Discussionmentioning
confidence: 99%
“…In childcare settings, two studies reported no change in sun exposure measured by parent reports or by change in melanocytic nevi in the children's skin [18,19,246], but one study did find that children spent less time outdoors during peak sun hours at childcare centers with sun protection policies [124]. One study also failed to produce changes in sunburn prevalence after an educational intervention with parents [18,19].…”
Section: Interventions In Childcare and School Settingsmentioning
confidence: 99%